2019
DOI: 10.4049/jimmunol.1801350
|View full text |Cite
|
Sign up to set email alerts
|

Effector and Activated T Cells Induce Preterm Labor and Birth That Is Prevented by Treatment with Progesterone

Abstract: Preterm labor commonly precedes preterm birth, the leading cause of perinatal morbidity and mortality worldwide. Most research has focused on establishing a causal link between innate immune activation and pathological inflammation leading to preterm labor and birth. However, the role of maternal effector/activated T cells in the pathogenesis of preterm labor/birth is poorly understood. In this study, we first demonstrated that effector memory and activated maternal T cells expressing granzyme B and perforin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
111
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(121 citation statements)
references
References 223 publications
(243 reference statements)
10
111
0
Order By: Relevance
“…This is consistent with the idea that baseline inflammation can blunt responses to stimuli (61). In fact, this could be entirely consistent with the inflammatory signatures identified in earlier studies (5,(17)(18)(19)(20)(21)(22)(23)(24), all of which were performed in the absence of an exogenous stimulus.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with the idea that baseline inflammation can blunt responses to stimuli (61). In fact, this could be entirely consistent with the inflammatory signatures identified in earlier studies (5,(17)(18)(19)(20)(21)(22)(23)(24), all of which were performed in the absence of an exogenous stimulus.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, elevated expression of the inflammatory cytokine tumor necrosis factor (TNF) in the amniotic fluid was associated with both infection and preterm birth (17). A recent study demonstrated that activated T cells are found at the maternal-fetal interface in women with spontaneous preterm delivery, and that, in a mouse model, treatment with progesterone can attenuate this inflammation and reduce risk of preterm birth (18).…”
mentioning
confidence: 99%
“…Importantly, at 24-34 weeks of gestation, we found that the single cell signatures of macrophages, monocytes, activated T cells, and fibroblasts were increased in the circulation of women with preterm labor and delivery compared to gestational age-matched controls (Figure 4E and S19B). These findings are in line with previous reports indicating a role for these immune cell-types in the pathophysiology of preterm labor 29, 6668 .…”
Section: Main Textsupporting
confidence: 93%
“…Other genes highly expressed by LED cells were CD34, CDH5, EDNRB, PDPN, and TIE1 (Figure 2C, S7). This finding conclusively shows the presence of lymphatic vessels in the decidua parietalis of the chorioamniotic membranes, providing a major route for maternal T cells infiltrating the maternal-fetal interface 29 .…”
Section: Main Textsupporting
confidence: 54%
“…Yet, several studies reported strong evidence that T cells, the primary cellular component of the adaptive immune system, are present at the maternal‐fetal interface . More recently, we provided evidence indicating that T cells are also implicated in the mechanisms that lead to labor at term and spontaneous preterm labor . However, the main humoral component of adaptive immunity, B cells, has been less investigated in the context of labor at term or preterm labor.…”
Section: Introductionmentioning
confidence: 83%